2006
DOI: 10.1080/02533950608628730
|View full text |Cite
|
Sign up to set email alerts
|

Why do People Disclose their HIV Status? Qualitative Evidence from a Group of Activist Women in Khayelitsha

Abstract: This study explores the bio-psychosocial context of HIV/AIDS in which eleven

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
(47 reference statements)
2
14
0
Order By: Relevance
“…While peer advocates are commonly used to increase medication adherence, an advocacy by HIV-infected women is not described in the literature (Almeleh, 2006; Hemsworth & Pizer, 2006; Iwelunmor, Zungu, & Airhihenbuwa).Our data support two general types of advocacy: formal employment as a counselor, or informally through sharing her story and encouraging other women to practice “safe” behaviors. This disclosure of HIV status was related to a self-acceptance of the chronic nature of the disease, itself an important self-management task (Swendeman, et al, 2009).…”
Section: Discussionsupporting
confidence: 59%
“…While peer advocates are commonly used to increase medication adherence, an advocacy by HIV-infected women is not described in the literature (Almeleh, 2006; Hemsworth & Pizer, 2006; Iwelunmor, Zungu, & Airhihenbuwa).Our data support two general types of advocacy: formal employment as a counselor, or informally through sharing her story and encouraging other women to practice “safe” behaviors. This disclosure of HIV status was related to a self-acceptance of the chronic nature of the disease, itself an important self-management task (Swendeman, et al, 2009).…”
Section: Discussionsupporting
confidence: 59%
“…The nature of the interaction between the respondents and PLWHA is, however, not known. As mentioned earlier, Almeleh (2006) found that in Cape Town HIV status disclosure is most common when people are sick and have no choice other than to disclose to potential care-givers and assistants. Consequently, HIV/AIDS is so strongly associated with illness and death that people whose health has been restored by HAART are regarded by some as no longer being HIV positive (Almeleh, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…As mentioned earlier, Almeleh (2006) found that in Cape Town HIV status disclosure is most common when people are sick and have no choice other than to disclose to potential care-givers and assistants. Consequently, HIV/AIDS is so strongly associated with illness and death that people whose health has been restored by HAART are regarded by some as no longer being HIV positive (Almeleh, 2006). Change in instrumental stigma 0.17*** n/a n/a [0.05] n/a n/a Change in symbolic stigma À0.06 n/a n/a [0.06] n/a n/a n 607 608 610 R-squared 0.10 0.12 0.28 Prob > F 0.000 0.000 0.000…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Perhaps this is why, when they weighed up the costs and benefits of disclosing, or choosing certain individuals to disclose to and not others, they did so to mitigate these bad reactions, and thus minimise the actual stigma and discrimination that they would receive. Almeleh (2006) found that his study participants weighed up the perceived negative responses towards one's HIV-positive status disclosure with the potential positive support that certain individuals could offer them, and ultimately chose to disclose to persons they trusted, who were of value to them and from whom very little or no negative reactions or outcomes were expected to result from the disclosure.…”
Section: Discussionmentioning
confidence: 99%